THE CONCEPT OF HALALAN THAYYIBAN ON THE ETHICS OF CONSUMPTION, PRODUCTION, AND DISTRIBUTION IN THE QUR’AN AND HADITH - Mufih, Betania Kartika (Pondok Pesantren Modern Islam Assalaam, 2023)
The concept of “Halalan Thayyiban” as it is described in the Qur’an and Hadith is examined in this paper along with its ethical implications for consumption, production, and distribution. The entire approach to nutrition is described in the verse from al-Baqarah: 168, “O people, eat from everything is on earth [that is] permissible and good or halalan thayyiban.” The term “eat” refers to more than just food consumption; it also refers to the ethical sourcing of food, its manufacture, including avoiding the use of tools from haram or dubious sources, as well as its storage, packaging, labelling, distribution, delivery, and adherence to fair trade principles. The phrase “from farm to fork” refers to the permissibility and wholesomeness along the entire supply chain. The only method of research used for this study was library research. The study discovered that by clarifying the halalan thayyiban ethical framework as specified in the Qur’an and Hadith, this paper adds to a greater comprehension of how Islamic ethics and current problems in the food sector interact.